The Effect of Light Emitting Diodes (LEDs) Spectra on Growth, Morphological and Genetic Stability of Eurycoma longifolia Hairy Root Cultures through ISSR and DAMD Analysis - Mahmoud Ali Khalaf Abushattal,; Sani Sale,; Sreeramanan Subramaniam,; Nor Hasnida Hassan,; Mohamad Fadhli Mad’ Atari, (Tropical Life Sciences Research, 2025)
Light quality significantly influences plant growth and development by interacting with photoreceptors, leading to reversible and irreversible outcomes. This study provides novel insights into the species-specific effects of light-emitting diodes (LEDs) on the morphological characteristics and genetic stability of Eurycoma longifolia hairy root cultures (ELHRCs) under different light qualities. LED treatments included white (400 nm–700 nm), blue (440 nm), mint green (530 nm), red (660 nm) and a combination of blue with red (1:1) (440 nm + 660 nm) applied for 8, 10 and 12 weeks. Morphological changes and growth were assessed alongside genetic stability through direct amplification of minisatellite DNA regions (DAMD) and inter-simple sequence repeat (ISSR) markers analysis using 12 primers. The results showed genetic similarity of 90.6% after 8 weeks and 100% after 10 and 12 weeks (DAMD) and 100%, 98.2% and 90.3% after 8, 10 and 12 weeks, respectively (ISSR) under all LED treatments, confirming the genetic stability of the hairy roots. Additionally, the study demonstrated how spectral quality influences hairy roots growth and morphology. The high percentage of genetic similarity highlights LEDs as a promising tool for in vitro culture of ELHRCs. These findings represent the first comprehensive report on the combined effects of LED spectral quality on growth, morphological changes and genetic stability in ELHRCs.